2023
DOI: 10.1021/acs.iecr.2c04492
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model for a Three-Phase Enzymatic Reaction System

Abstract: The enzymatic reaction system with a solid−liquid−gas three-phase interface microenvironment allows oxygen to be directly supplied to the oxidase catalytic reaction from the gas phase, effectively improving enzyme kinetics as compared with the conventional two-phase system. For this new system, a mathematical model is developed in this work to describe the enzymatic reaction coupled with interphase mass transfer, by which the influences of three-phase interfacial microenvironment on reaction kinetics can be sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 30 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…As shown in Figure 2A2, the production rate of H 2 O 2 remains high regardless of the porosity. Since the previous study 20 confirmed that the supply rate of oxygen dominantly determines the production rate of H 2 O 2 , this high production rate can be attributed to the fact that the supply rate of oxygen is sufficiently large (see Figure 2A1). Furthermore, the supply rate of oxygen is related to the structure of the porous substrate.…”
Section: Heterogeneous Electrochemical Reactionmentioning
confidence: 70%
See 4 more Smart Citations
“…As shown in Figure 2A2, the production rate of H 2 O 2 remains high regardless of the porosity. Since the previous study 20 confirmed that the supply rate of oxygen dominantly determines the production rate of H 2 O 2 , this high production rate can be attributed to the fact that the supply rate of oxygen is sufficiently large (see Figure 2A1). Furthermore, the supply rate of oxygen is related to the structure of the porous substrate.…”
Section: Heterogeneous Electrochemical Reactionmentioning
confidence: 70%
“…This phenomenon has been confirmed in the previous study. 20 In addition, the escape rate of H 2 O 2 also increases with increasing porosity. This is because the pore size increases with increasing porosity when the pore wall thickness is fixed.…”
Section: Effect Of the Porosity Of The Substratementioning
confidence: 99%
See 3 more Smart Citations